Comunicação, tempo, história: tecendo o cotidiano em fios jornalísticos - Matheus, Leticia Cantarela (2010)
The journalistic threads with which everyday life is entwined are the narrative articulations that this thesis analyzes. It investigates the temporal identity of journalistic narratives and the value that time plays for such a type of communication, by checking the contributions of journalism to the perception of social time. This research also investigates the notions of time that contribute to its legitimacy, while separating journalistic narrations into the production of past, present and future. The thesis purposes analyze these productions in two ways as commemorations and as events - and investigates the need to celebrate the past and the ways that this celebration experience takes as history, as tradition and as memory, three different strategies of narratives of bygone days. It also notes the participation of the past in the construction of news, a particular form of producing events, different from that held by the historiographical operation. We present a typology of the uses of time in daily narratives of three newspapers with more than one hundred years in Rio de Janeiro: Jornal do Commercio, O Fluminense and Jornal do Brasil. These uses of time expose some functions performed by journalistic practices in everyday life, especially that of counting the course of time, either fixing it or potentiating its flow effect. Then, this thesis shows the concepts of history involved in these journalistic emplotments and, in a broader approach, investigates the long-term processes of signifying journalism by the different connections we have established over time with this social practice. Finally, we highlight the importance of journalistic narratives to frame multiple consciousness of history, due to their daily work of synthesizing gates to other times, whether to the past or to the future or even to the present as an extended territoriality larger than experiences personally attended. We tend to approach journalism as a particular form of social interaction, defined by a specific experience based on the periodicity and for whom most of its history has been based on the expectation and the generation of novelties.